Evaluation of By-Pass Protein and Urea for Wool Production - Mathur, O P (Annals of Arid Zone, 2016)
Studies on the comparative efficacy of utilization of native protein vis a vis by-pass protein with or without urea was conducted to assess the biological response on wool production, quantitatively and qualitatively. The wool production was highest in lambs fed by-pass protein. Staple length, staple crimps were found to increase, and modullation percentage was found to decrease. with the advancement of age in all the animals irrespective of treatment received.